Improving Students’ Reading Comprehension by Using SQ3R Method - Syahfutra, Wandi (State Islamic University of Sultan Syarif Kasim Riau, 2017)
Reading is one of the most important components of any language and it is an essential tool for long-life learning. The goal of reading is comprehension. In order to comprehend reading passage, students need to apply some methods to help them. This study aimed at improving students’ reading comprehension and motivation by using SQ3R method. SQ3R system has been used successfully for many years and the system has proven effective in increasing students’ retention. Student learning centres on a complex problem that does not have a single correct answer. Students work in collaborative groups to identify what they need to learn in order to improve their reading comprehension.. From the test, it was obtained that the lower score is 64 and the higher score is 88. The mean is 81.03. The data were obtained from the research by using SPSS. Overall, the results showed that students’ reading comprehension could be improved by using SQ3R method were identified.